Conservation gap analysis of crop wild relatives in Turkey. Issue 2 (8th January 2019) - Tas, Necla; West, George; Kircalioglu, Gun; Topaloglu, S. Boyraz; Phillips, Jade; Kell, Shelagh; Maxted, Nigel
Abstract: Crop wild relatives (CWR) are wild plant taxa relatively closely related to crops that can contribute beneficial traits for crop improvement, such as biotic and abiotic stress resistance. Turkey has a rich flora of approximately 11, 000 higher plant taxa, has two Vavilov centres of crop diversity (i.e. the Mediterranean and the Near East), is recognized as the cradle of agriculture providing the northern boundary of the Fertile Crescent, and has recently been identified as the country with the highest concentration of CWR diversity. The objective of this paper is to present the results of a gap analysis of CWR genetic diversity in Turkey using existing data sources of 458 of the 764 priority CWR taxa with available georeferenced data. In total, 27, 597 presence points were obtained from the Global Biodiversity Information Facility, Aegean Agricultural Research Institute in Menemen and Field Crops Central Research Institute, Ankara. Geographic Information System (GIS) software was used to identify taxon richness, sampling bias, future ex situ population collection and location where existing protected sites could form the basis of national network of in situ genetic reserves. CWR taxon richness was located along the Aegean Coast, Syrian border and southern Mediterranean coast. Current ex situ representation of CWR taxa is inadequate and further collection across the entire country is required. The highest priority in situ reserve location is found in Izmir, Sanliurfa and Antalya province, which reflects overall CWR richness.